Judicial Review Of Parliamentary Oversight on The Issuance of the Job Creation Emergency Law from the Check and Balances Perspective - Firna Dwi Ananda; Muhamad Aksan Akbar; Syamsul Rijal (Sangia Nibandera Law Research, 2026)
This study aims to analyze the mechanism of the implementation of the House of Representatives (DPR) oversight function towards the issuance of Government Regulation in Lieu of Law (Perppu) based on the 1945 Constitution and evaluate the application of the principle of checks and balances in the procedure of issuance and approval of Perppu Number 2 of 2022 concerning Job Creation into Law Number 6 of 2023. The research method used is normative legal research with a statutory approach, a conceptual approach, and a case approach. The results of the study indicate that normatively, the 1945 Constitution has explained a strong mechanism of checks and balances where the DPR acts as a constitutional gateway through its legislative and supervisory functions to test the President's subjectivity regarding the parameters of "compelling urgency" as stipulated in the Constitutional Court Decision Number 138/PUU-VII/2009. However, the fact that the ratification of the Perppu on Job Creation indicates a weakening of the principle of checks and balances and is merely a mere formality. The House of Representatives (DPR) tends to ignore substantive material review and bypass emergency parameters to accommodate executive-heavy policies, as well as ignoring Constitutional Court Decision No. 91/PUU-XVIII/2020 concerning the obligation for meaningful public participation. This study recommends the need to codify the standard parameters of constitutional emergencies and strengthen parliamentary institutional independence.